Rekayasa Kualitas Jagung Manis (Zea Mays L. Saccharata) Varietas Patagon Melalui Aplikasi Pupuk KCl Dan Umur Panen - Sahida Reza Wardana; Anis Sholihah; Anis Rosyidah (AGRONISMA, 2022)
Sweet corn is a plant that contains carbohydrates, protein, vitamins and high sugar content but low in fat and good taste. Currently the production of sweet corn is relatively low, due to the application of inorganic fertilizers with inappropriate doses, in addition, the harvesting time of corn is a differentiating factor for the physico-chemical structure of corn kernels. Based on this, it is necessary to do research and the results can be used as a basis for fertilizer application, especially potassium fertilizer and the right harvest time. Experimental research on farmers' land in Tlogomas Malang City with an altitude of 667 m above sea level, an average temperature of 25oC, 81% humidity and clay textured soil. The study was carried out from December 2021 to March 2022. The study was arranged using a factorial randomized block design (RAK) with control, the first factor being KCl fertilizer dose 2 levels: D1 = 100 kg ha-1 and D2 = 200 kg ha-1. The second factor of harvesting age consisted of 3 levels: P1 = 68 DAP, P2 = 73 DAP and P3 = 78 DAP and Control = without KCl fertilizer. Each treatment combination was repeated three times, so there were 21 treatment plots with 10 plant samples. The results showed a significant interaction between KCl fertilizer and harvest age on the yield and quality of sweet corn of Paragon variety. The treatment dose of KCl fertilizer 200 kg ha-1 at harvest age of 78 DAP resulted in fresh weight of cobs per plant, fresh weight of cobs per tonne hectare and the highest level of hardness compared to other treatments with successively 254.96 g per plant, 30.27 tons. ha -1 and 16.67 mm/g/s. There was no significant difference between doses of KCl fertilizer on total dissolved solids, carbohydrate content and water content with successive values of 7.56 Obrix; 25.39%; and 75.47% water content.